Open-channel microfluidic device for TiO2NTs@Fe3O4NPs-assisted viral RNA extraction and amplification-free RNA fluorescence status evaluation - Matějková, Nikola; Smělá, Denisa; Beránek, Martin; Čapek, Jan; Michalcová, Lucie; Michálková, Lenka; Svoboda, Jakub; Škereň, Marek; Svobodová, Zuzana; Sopha, Hanna Ingrid; Macák, Jan; Korecká, Lucie; et al. (My University, 2024)
Most routine viral RNA detection assays available today rely on RNA amplification steps. The sensitivity of such methods comes at the expense of time, cost, and equipment availability. Given the constraints during the COVID-19 pandemic, such as the limited capacity of RNA amplification instruments and the global shortage of isolation kits, there has been a demand for amplification-free assays which should meet POCT criteria: affordable, sensitive, specific, user-friendly, rapid, and equipment-free. This study aims to design and validate a microanalytical system for direct viral RNA detection which meets these criteria. The presented RNA detection assay consists of four consecutive steps: immunocapturing viral particles, viral particles lysis, TiO2NTs@Fe3O4NPs-assisted RNA extraction, and finally viral RNA detection. The last three steps occur within a microfluidic device with open channels (OC-MFD). The OC-MFD is manufactured from polycarbonate film by unique mechanical replication techniques in a roll-to-roll setup. This method has been experimentally validated to offer the advantages of low-cost and extremely rapid production (1 mil. pieces of OC-MFDs per hour). Two permanent magnets situated under the application/extraction zones enabled to fix magnetically active particles/nanotubes. At first, viral particles are quantitatively captured from the entire sample volume using immunomagnetic particles. The lysed viral particles are transferred to the application zone of OC-MFD, followed by RNA extraction using magnetic TiO2 nanotubes decorated with Fe3O4 nanoparticles (TiO2NTs@Fe3O4NPs). The effectivity of the nanomaterial to attract viral RNA molecules was evaluated against a standard RT-qPCR-based laboratory test. Equivalence tests were performed with 143 positive and negative SARS-CoV-2 samples. Spearman rank correlation coefficients demonstrated high agreement for both measured biomarker genes (the E gene equaled 0.76, the RdRp gene equaled 0.73, the p-value < 0.001). To fulfill POCT criteria, viral RNA captured directly on the surface of TiO2NTs@Fe3O4NPs and fixed by permanent magnet in the extraction zone of OC-MFD was visualized in situ using SYBR Green II fluorescent dye. This strategy allows to achieve a sensitivity of 0.3 ng of RNA per µL−1. Additionally, this test can be easily adapted for direct detection of any other RNA virus simply by choosing a suitable immunosorbent with the corresponding antibody specificity. Besides, the most significant advantages of this microanalytical system for direct viral RNA detection and outlook for future applications are also discussed and summarized.
Mikrofluidní zařízení s otevřeným kanálem pro extrakci virové RNA za asistence TiO2NTs@Fe3O4NPs a hodnocení fluorescenčního stavu RNA bez amplifikace
Keywords: RNA virus; Immunocapturing; RNA extraction; TiO2 nanotube; Open-channel microfluidic device; Fluorescence detection; RNA virus; imunokapturace; extrakce RNA; TiO2 nanotrubice; mikrofluidní zařízení s otevřeným kanálem; fluorescenční detekce